Challenges to Value-Enhancing Innovation in Health Care Delivery: Commonalities and Contrasts with Innovation in Drugs and Devices - Garber, Steven (Rand Health Q, 2012)
Limiting the growth of health care costs while improving population health is perhaps the most important and difficult challenge facing U.S. health policymakers. The role of innovation in advancing these social goals is controversial, with many seeing innovation as a major cause of cost growth and many others viewing innovation as crucial for improving the quality of care and health outcomes. The authors argue that mitigating the tension between improving health and controlling costs requires more-nuanced perspectives on innovation. More specifically, they argue that policymakers should carefully distinguish between innovative activities that are worth their social costs and activities that are not worth their social costs and try to encourage the former and discourage the latter. The article considers innovation in drugs, devices, and methods of delivering health care, with particular attention to delivery.